2017
DOI: 10.1186/s40409-017-0102-2
|View full text |Cite
|
Sign up to set email alerts
|

Agaricus brasiliensis polysaccharides stimulate human monocytes to capture Candida albicans, express toll-like receptors 2 and 4, and produce pro-inflammatory cytokines

Abstract: Background Agaricus brasiliensis is a medicinal mushroom with immunomodulatory and antitumor activities attributed to the β-glucans presented in the polysaccharide fraction of its fruiting body. Since β-glucans enhance cellular immunoresponsiveness, in this study we aimed to evaluate the effect of an acid-treated polysaccharide-rich fraction (ATF) of A. brasiliensis on the ability of human monocytes to adhere/phagocyte C. albicans yeast cells, their expression of pattern recognition receptors and their ability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
0
3
0
3
Order By: Relevance
“…This enhanced immune response is accomplished by an increased proinflammatory cytokine and chemokine production and an enhanced oxidative burst, as mainly demonstrated in mouse models [38]. As shown in Table 1, biologically active fungal β-glucans found in edible mushrooms (e.g., Agaricus brasiliensis, Pleurotus citrinopileatus, Agaricus blazei, Flammulina velutipes) can enhance inflammatory cytokine production in monocytes [39][40][41]43,44] as well as in monocyte-derived macrophages (MDM) [40]. Furthermore, Minato and colleagues have recently explored the functional effect of Pleurotus citrinopileatus polysaccharide (PCPS) on monocyte-to-macrophage differentiation, finding that PCPS can direct Dectin-1 and TLR2-mediated differentiation of monocytes toward a macrophage cell population with reduced proinflammatory capacity [43].…”
Section: In Vitro Effects On Innate Immunity Cellsmentioning
confidence: 90%
See 1 more Smart Citation
“…This enhanced immune response is accomplished by an increased proinflammatory cytokine and chemokine production and an enhanced oxidative burst, as mainly demonstrated in mouse models [38]. As shown in Table 1, biologically active fungal β-glucans found in edible mushrooms (e.g., Agaricus brasiliensis, Pleurotus citrinopileatus, Agaricus blazei, Flammulina velutipes) can enhance inflammatory cytokine production in monocytes [39][40][41]43,44] as well as in monocyte-derived macrophages (MDM) [40]. Furthermore, Minato and colleagues have recently explored the functional effect of Pleurotus citrinopileatus polysaccharide (PCPS) on monocyte-to-macrophage differentiation, finding that PCPS can direct Dectin-1 and TLR2-mediated differentiation of monocytes toward a macrophage cell population with reduced proinflammatory capacity [43].…”
Section: In Vitro Effects On Innate Immunity Cellsmentioning
confidence: 90%
“…The regulation of additional cellular responses by mushroom-derived β-glucans in monocytes and DC has been also described. Specifically, β-glucans from Agaricus brasiliensis, Agaricus blazei or Flammulina velutipes extracts with immunomodulatory and antitumor activities, significantly increase the adherence and phagocytosis by monocytes [39][40][41] and enhance ROS production in monocytes and macrophages [40], while water-soluble components from Armillariella mellea or Hericium erinaceum decrease the MDDC endocytic capacity [46,47]. Besides β-glucans from yeasts and mushrooms, also those derived from cereals influence MDDC functions.…”
Section: In Vitro Effects On Innate Immunity Cellsmentioning
confidence: 99%
“…Once binding to the dectin-1, as the most important receptor, β-glucan stimulates the production of many cytokines or activates other immune and nonimmune reaction mechanisms [69]. Martins et al demonstrated that a polysaccharide-rich fraction of Agaricus brasiliensis is able to regulate the host response by activating both pro-and antiinflammatory mechanisms, thus increasing the production of TNF-α and IL-1β by human monocytes through modulation of Toll-like receptor 4 and Toll-like receptor 2 expression [70]. In addition, even after TLR blockade, these polysaccharides still activated the monocytes to produce considerable levels of IFN-γ, IL-1β, and IL-10.…”
Section: The Effect Of Natural Polysaccharide Structure In Wound Healmentioning
confidence: 99%
“…4 | DISCUSSÃONeste estudo, mesmo que de forma ligeira, que o cogumelo A. brasiliensis provou ser capaz de modular a resposta imunológica de tilápias do Nilo no que diz respeito ao A. brasiliensis(MARTINS, 2017; tenha sido perdida em teleósteos(TANEKHY, 2016), explicando assim, a resposta imunomoduladora baixa frente a suplementação.Outro fato que deve ser levado em consideração e de que para imunoestimulantes, como o β-glucanos, a via de administração é um fator determinante na resposta imunológica, principalmente tratando-se de tilápias, uma vez que a oferta de imunoestimulantes via alimentação produz efeito atenuante nas células do sistema imunológico quando comparada a oferta via imersão e injeção intraperitoneal, no que diz respeito a contagem de monócitos, leucócitos e linfócitos. (SADO et al, 2016).…”
unclassified